1974
DOI: 10.1177/002182867400500204
|View full text |Cite
|
Sign up to set email alerts
|

Saturn and His Anses

Abstract: For Saturn alone stands apart from the pattern of the remaining celestial bodies, and shows so many discrepant phases, that hitherto it has been doubted whether it is a globe connected to two smaller globes or whether it is a spheroid provided with two conspicuous cavities or, if you like, spots, or whether it represents a kind of vessel with handles on both sides, or finally, whether it is some other shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 1 publication
0
18
0
1
Order By: Relevance
“…Most observers thought that Saturn's features were due to satellites, and that is what they reported seeing when they observed Saturn. However, other astronomers believed that Saturn had a ring, and they reported seeing a ring when they observed Saturn (Helden, 1974). But it seems to us that no one who views one of the unambiguous photographs taken by one of the Voyager spacecraft could possibly doubt that Saturn is encircled by a ring.…”
Section: Characteristic 2 Ambiguity Of the Datamentioning
confidence: 99%
“…Most observers thought that Saturn's features were due to satellites, and that is what they reported seeing when they observed Saturn. However, other astronomers believed that Saturn had a ring, and they reported seeing a ring when they observed Saturn (Helden, 1974). But it seems to us that no one who views one of the unambiguous photographs taken by one of the Voyager spacecraft could possibly doubt that Saturn is encircled by a ring.…”
Section: Characteristic 2 Ambiguity Of the Datamentioning
confidence: 99%
“…9 A newsletter printed in The Hague early in October was sent to the major European cities in diplomatic pouches, 10 and a French soldier departed from The Hague for Paris with knowledge of how to make spyglasses. 11 In November, the newsletter was received by Paolo Sarpi, who shared its content with Galileo. 12 We can get some idea of what Galileo's first, three-powered spyglass looked like from a sketch made in August 1609 of the first actual spyglass to arrive in Naples, by the internationally known polymath, Giambaptista della Porta (Fig.…”
Section: Galileo's Telescopementioning
confidence: 99%
“…In his third sunspot letter, printed in 1613, Galileo reported that since there had been no change in the positions of Saturn's "companions," he had lost interest, but that when he happened to look at the planet again in 1612 he was surprised to see the appendages gone. Had Saturn devoured his children [11]? Since Saturn's appearance was neutral in the debate between the world systems, the problem was only occasionally discussed until the 1640s, when a new generation of telescopic observers usually armed with better telescopes took on the problem.…”
Section: The Long Refractor and Further Discoveriesmentioning
confidence: 99%
“…When human perception is at its limits, even basic observations are unreliable, and may be biased towards what the observer expects to see. Van Helden surveyed the history of early telescopic observations of Saturn 8 . While most observers today, even with very low-resolution pictures, see a planet with rings, early observers echoed Galileo's first observations, and saw and reported on a planet with two giant moons, one on each side.…”
Section: Observationsmentioning
confidence: 99%